IMPLEMENTASI POS ARENA BERMAIN ANAK TERHADAP PELAYANAN PUBLIK DI BAPAS KELAS II PATI (IMPLEMENTATION OF POS COURT PLAYING CHILDREN AGAINST PUBLIC SERVICES IN CORRECTIONAL OFFICE CLASS II PATI ) - Muhammad Ceres Yusuf Althuhr (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Anyone from government administrators can obtain public services. Among them are facilities for children, parents, disabled clients, and pregnant women. Here the author makes the Post Playground Innovation Children as a form of public service in Pati Class II Correctional Institution. The author sees in Bapas Class II Pati still does not have a room that is devoted to children, even though visitors and clients in Bapas are children. The method used is descriptive using qualitative. Post Playground Innovation is product innovation. And product quality can be seen from 5 dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy.